Literature and subjection : the economy of writing and marginality in Latin America - Legras, Horacio (Illuminations (Pittsburgh, Pa.), 2008)
"Through theoretical, philosophical, cultural, political, and historical analysis, Horacio Legras views the myriad factors that have both formed and stifled the integration of peripheral experiences into Latin American literature. Despite these barriers, Legras reveals a handful of contemporary authors who have attempted in earnest to present marginalized voices to the Western world. His deep and insightful analysis of key works by novelists Juan José Saer (The Witness), Nellie Campobello (Cartucho), Roa Bastos (Son of Man), and Jose María Arguedas (The Fox from Up Above and the Fox from Down Below), among others, provides a theoretical basis for understanding the plight of the author, the peripheral voice and the confines of the literary medium. What emerges is an intricate discussion of the clash and subjugation of cultures and the tragedy of a lost worldview."--Publisher's description.